Microenvironment meets lineage complexity in junctional tumorigenesis - Wa Xian (Nature Portfolio, 2019)
Using a sensitizing genetic model, Moon and colleagues provide compelling data for a determinant role of microenvironment in tumorigenesis, and lend support to the notion that such influences can be pharmacologically dampened to reduce the onset of cancers.